Structural and magnetic depth profiles of magneto-ionic heterostructures beyond the interface limit - Dustin A. Gilbert (Nature Portfolio, 2016)
Mechanisms allowing electrical manipulation of magnetic material possess potential applications in low power memory and sensor technologies. Here, the authors demonstrate the control of magnetic characteristics via voltage-driven migration of oxygen across a GdOx/Co interface, well into the bulk of the cobalt.